Akuntansi Manajemen sebagai Katalisator Nilai Bisnis: Pendekatan Strategis pada Pengendalian Biaya dan Kinerja UMKM - Novita, Lola; Sari, Ratna Deli (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2026)
Micro, Small, and Medium Enterprises (MSMEs) face intense competitive pressures that demand sustainable business efficiency and effectiveness. This conceptual article aims to explore and formulate the role of management accounting as a catalyst for business value through a Strategic Cost Management (SCM) approach within the MSME sector. Utilizing a literature review method, this study synthesizes recent academic publications relevant to management accounting and organizational governance. The synthesis reveals three main findings. First, there is an urgent need to transform the management accounting paradigm from a mere backward-looking administrative record-keeper into a forward-looking strategic business partner. Second, MSMEs must abandon traditional cost-cutting practices that risk degrading product quality and transition to SCM. SCM implementation focuses efficiency rationality on eliminating non-value-added activities and applying target costing. Third, this article formulates a comprehensive conceptual framework that integrates the provision of multidimensional information (input), the execution of SCM instruments (process), and performance measurement through an adapted Balanced Scorecard (output) to generate sustainable business value creation (outcome). In conclusion, integrating management accounting functions enables MSMEs to control operational costs without degrading their competitive advantage. Practically, this study recommends that MSME owners improve financial literacy and adopt accounting system technologies to design resilient performance strategies.